Performance of the anammox process treating low-strength municipal wastewater under low temperatures: Effect of undulating seasonal temperature variation. (September 2020) - Gong, Xiaofei; Wang, Bo; Qiao, Xin; Gong, Qingteng; Liu, Xuefan; Peng, Yongzhen
Graphical abstract: Highlights: NRR decline in (17.9 → 15.1 °C) was nearly threefold higher than that in (22.2 → 17.9 °C). Contribution of anammox to N loss was greater at 15.1 °C (91.7%) than 21.9 °C (78.9%). Denitrifying bacteria was more sensitive than AnAOB to low temperature in winter. Ca. Brocadia could adapt to lower temperature after short-term acclimatization. Abstract: In the anammox process treating low-strength municipal wastewater, the effect of common seasonal temperature variation (15.1 °C–22.2 °C) on performance was studied. In autumn and winter, the nitrogen removal rate (NRR) decrement of 0.038kgN/(m 3 ·d) (17.9 °C → 15.1 °C) was nearly threefold higher than 0.014kgN/(m 3 ·d) (22.2 °C → 17.9 °C), which showed that lower temperature laid more negative impact on nitrogen removal. 15 N isotope tracing tests confirmed that the contribution of denitrification to nitrogen removal was far less than anammox, and anammox contributed more at 15.1 °C (91.7%) than 21.9 °C (78.9%). Anammox bacteria could adapt to lower temperature after short-term acclimatization, especially the dominant genus Ca. Brocadia increased from 1.8% to 2.5% and its abundance was significantly correlated with nitrogen consumption (p < 0.05). Above findings suggest that the adaptability of Ca. Brocadia could provide the possibility to maintain nitrogen removal performance at lower temperature. In spring, the improved maximum anammox activity from 2.85 to 3.23mgNH4 + -N/(gVSS·h) indicated the recovered removal capacity.